Straight Line Foraging in Yellow-Eyed Penguins: New Insights into Cascading Fisheries Effects and Orientation Capabilities of Marine Predators - Mattern, Thomas (Public Library of Science, 2013)
Free-ranging marine predators rarely search for prey along straight lines because dynamic ocean processes usually require complex search strategies. If linear movement patterns occur they are usually associated with travelling events or migratory behaviour. However, recent fine scale tracking of flying seabirds has revealed straight-line movements while birds followed fishing vessels. Unlike flying seabirds, penguins are not known to target and follow fishing vessels. Yet yellow-eyed penguins from New Zealand often exhibit directed movement patterns while searching for prey at the seafloor, a behaviour that seems to contradict common movement ecology theories. While deploying GPS dive loggers on yellow-eyed penguins from the Otago Peninsula we found that the birds frequently followed straight lines for several kilometres with little horizontal deviation. In several cases individuals swam up and down the same line, while some of the lines were followed by more than one individual. Using a remote operated vehicle (ROV) we found a highly visible furrow on the seafloor most likely caused by an otter board of a demersal fish trawl, which ran in a straight line exactly matching the trajectory of a recent line identified from penguin tracks. We noted high abundances of benthic scavengers associated with fisheries-related bottom disturbance. While our data demonstrate the acute way-finding capabilities of benthic foraging yellow-eyed penguins, they also highlight how hidden cascading effects of coastal fisheries may alter behaviour and potentially even population dynamics of marine predators, an often overlooked fact in the examination of fisheries’ impacts.